KEBEBASAN TERSANGKA MEMBERIKAN KETERANGAN DALAM PROSES PENYIDIKAN - Barhamudin, Barhamudin (Faculty of Law, University of Palembang, 2024)
The aim of the research is to determine the form of protection of suspects' rights in the investigationprocess and to find out what obstacles suspects face in exercising their rights in the investigationprocess. This research is normative legal research which uses secondary data which includes: a.Primary legal materials b. Secondary legal materials and c. Tertiary legal materials. The researchresults showed that suspects must be free to provide information during investigations and trials alongwith their rights.